(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the Indian man-dominated society, women faced terrific problems since vedic period due to superstitions and misguided rituals. The women have been victimised through different ways, like-child marriage, sati pratha, parda pratha, restriction to widow remarriage, widow’s exploitation, devadasi system etc. So, incidentally taking birth as woman had been treated as a curse for the woman. That system insipid the women and brought inferiority complex which proved a big hurdle in their social, economic and personal development. During British rule in India and after independence Dr. B.R. Ambedkar fought for the rights of women and made such provisions in constitution of India so that women must be treated equally in the society. The provision of equality to women made for all streams whether it is education, employment, social and economic rights. It is only due to Dr. Ambedkar that today women feel self-confident and self dependent. The implementation of many articles of constitution and laws brought self-confidence, individuality, self-respect and overall empowerment for women. The empowered women have proved themselves better than men in all fields be it education, entrepreneurship, medical, engineering and defence etc. The old ill trusted traditions disappeared to a large extent gradually from the society only due to the hard efforts put by Dr. Ambedkar. However, due to absence of strong judicial and administrative system and ignorance of laws women become victimized by various social evils such as child bearing, family care roles, deep rooted cultural norms etc. and become target of discrimination, exploitation and domestic violence. Women Empowerment is the vital instrument to expand women’s ability to have resources and to make strategic life choices. This present paper attempts to examine the status of women in India and their empowerment through Dr. Ambedkar in India. It tries to highlight the issues and challenges related to women in Indian society and eradication of such impediments though Ambedkarite approach. Through this paper it is tried to verify the relevance of Dr. Ambedkar approach for upliftment of economic, social and political status of women.